2016
DOI: 10.1139/cjz-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites of gray wolves (Canis lupus) in northern and western Canada

Abstract: Gray wolves (Canis lupus L., 1758) are mobile opportunistic predators that can be infected by a wide range of parasites, with many acquired via predator–prey relationships. Historically, many of these parasites were identified only to genus or family, but genetic tools now enable identification of parasite fauna to species and beyond. We examined 191 intestines from wolves harvested for other purposes from regions in the Northwest Territories, British Columbia, Saskatchewan, and Manitoba. Adult helminths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…For example, Rausch reported that in a randomly collected sampling of 200 wild canids in the Brooks Range of Alaska, ≈30% were infected with E. canadensis tapeworms. This finding is similar to Schurer et al’s ( 15 ) recent report indicating infections in 37% (71/191) of wolves sampled across Canada. Rausch ( 16 ) found 24% (24/101) of moose infected in an agricultural region of southern Alaska, and 4% (1/23) of moose infected in the Anchorage area.…”
Section: Echinococcus Spp Tapeworms and Echinococcosis In Alaska Andsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, Rausch reported that in a randomly collected sampling of 200 wild canids in the Brooks Range of Alaska, ≈30% were infected with E. canadensis tapeworms. This finding is similar to Schurer et al’s ( 15 ) recent report indicating infections in 37% (71/191) of wolves sampled across Canada. Rausch ( 16 ) found 24% (24/101) of moose infected in an agricultural region of southern Alaska, and 4% (1/23) of moose infected in the Anchorage area.…”
Section: Echinococcus Spp Tapeworms and Echinococcosis In Alaska Andsupporting
confidence: 91%
“…Rausch’s ( 11 ) comprehensive review of E. canadensis tapeworms provides extensive information regarding the strongly endemic cycles he and others observed from the 1950s to the late 1990s throughout Alaska, Canada, and other Arctic countries. Likewise, readers are directed to Schurer et al’s ( 14 , 15 ) reviews of ungulate and wolf infections.…”
Section: Echinococcus Spp Tapeworms and Echinococcosis In Alaska Andmentioning
confidence: 99%
“…the parasite has recently been detected in wolves (Canis lupus) in taiga and boreal regions of the southern Northwest Territories and northern British Columbia (Gesy et al, 2014;Schurer et al, 2014aSchurer et al, , 2016. p0600…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The historical distribution of E. multilocularis in Canada encompasses two disjunct geographic areas: Northern Tundra Zone and North Central Region, both involving different predator-host communities ( Eckert et al, 2001 ). However, recent findings of the parasite in areas previously considered as nonendemic suggest an expansion of its geographic range ( Schurer et al, 2013b , 2016 ; Gesy et al, 2014 ). This parasite circulates primarily through smaller canids as definitive hosts: foxes ( Vulpes spp.)…”
Section: Introductionmentioning
confidence: 95%